Overcoming Challenges in Conducting Clinical Trials in Minority Populations: Identifying and Testing What Works - Romuladus E. Azuine, DrPH, RN; Sussan E. Ekejiuba, DVM, PhD (Global Health and Education Projects, Inc., 2014)
Participation in clinical trials is one of the greatest gifts that humanity can give to the fields of medicine and public health. Clinical trials are central in public health's mission to advance drug discovery.  The enrollment and retention of participants, especially minority populations, is one of the most practical challenges of successfully implementing a clinical trial.  In spite of these challenges, there are many reasons why a broader public participation in clinical trials is critical. The ability to generalize the scientific findings and the principles of equity, justice, and beneficence require an equitable distribution of the risks, benefits, and burdens of research for all classes and groups of people.  A new methodology article published in this journal presents a promising framework for addressing minority recruitment and retention using what is known and using it innovatively to address a difficult problem facing clinical trials and public health.  The innovative application of what is known in addressing a challenging problem, as this article presents, is worth the reading of all those interested in scientifically rigorous and ethically sound clinical trials that substantially comprise of diverse populations. Key words:  Clinical trials • Minority enrollment challenges • Global health • Research Ethics Copyright © 2015 Azuine et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.